2022
DOI: 10.1002/cctc.202200754
|View full text |Cite
|
Sign up to set email alerts
|

Waste‐Derived Copper‐Lead Electrocatalysts for CO2 Reduction

Abstract: It remains a real challenge to control the selectivity of the electrocatalytic CO 2 reduction (eCO 2 R) reaction to valuable chemicals and fuels. Most of the electrocatalysts are made of non-renewable metal resources, which hampers their largescale implementation. Here, we report the preparation of bimetallic copper-lead (CuPb) electrocatalysts from industrial metallurgical waste. The metal ions were extracted from the metallurgical waste through simple chemical treatment with ammonium chloride, and Cu x Pb y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…By using industrial metallurgical wastes as raw materials, Yang et al extracted Cu and lead (Pb) from industrial wastewater by electrodeposition, preparing a series of copper-lead (Cu x Pb y ) materials as CO 2 RR catalysts. 33 It is found that there is a synergistic effect between Cu and Pb in the prepared bimetallic electrocatalysts, especially, the Cu + and Pb 2+ species that can be reduced to Cu 0 and Pb 0 metal. The reduced species play an important role in the formation of CO, which promotes the enhancement of CO selectivity (the amount of CO formed at −1.05 V vs. RHE is about 4 times that of pure Cu).…”
Section: Waste To Wealth In Electrocatalysismentioning
confidence: 93%
See 2 more Smart Citations
“…By using industrial metallurgical wastes as raw materials, Yang et al extracted Cu and lead (Pb) from industrial wastewater by electrodeposition, preparing a series of copper-lead (Cu x Pb y ) materials as CO 2 RR catalysts. 33 It is found that there is a synergistic effect between Cu and Pb in the prepared bimetallic electrocatalysts, especially, the Cu + and Pb 2+ species that can be reduced to Cu 0 and Pb 0 metal. The reduced species play an important role in the formation of CO, which promotes the enhancement of CO selectivity (the amount of CO formed at −1.05 V vs. RHE is about 4 times that of pure Cu).…”
Section: Waste To Wealth In Electrocatalysismentioning
confidence: 93%
“…29,30 Even industrial waste materials such as copper in waste wire, steel wire in waste tires, silicon in waste photovoltaic materials, various metals in waste circuit boards, and valuable metals and elements in solid or liquid wastes contribute to a large market prospect for reutilization. 25,[31][32][33] To date, a few reviews have been published on the utilization of biomass derived electrocatalysts in energy storage that focus on the synthetic strategies and functionalization. 7,34,35 A review was recently published on the design of electrocatalysts from waste and natural materials.…”
Section: Xun Jiangmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the rise of synthesis strategies for nanoparticles with well-defined surfaces (i.e., anisotropic growth of nanowires or nanoplatelets) , and compositions (e.g., bimetallic, alloys, heteronanostructures) ,,, has further expanded the library of products that can be obtained through CO 2 reduction at high conversion rate. As a result, many tunable (bi)­metallic electrocatalysts have emerged as a viable strategy to tailor the electrocatalytic CO 2 reduction reaction (eCO 2 RR) for the selective production of valuable base chemicals and fuels. ,, For example, Cu–Ag dimers and heterostructures have been synthesized, which displayed CO 2 to CO conversion on Ag sites, and CO spillover and concomitant CO–CO coupling on Cu, resulting in boosted ethylene production compared to the monometallic counterparts. , Furthermore, it has been shown that combinations of Cu with post-transition metals (e.g., Sn) results in near unity CO production, whereas neither Cu nor Sn is very selective for CO on its own . Interestingly, bimetallic configurations are inferred to come with an additional benefit: doping of a secondary metal induces NP stabilization due to nanoscale strain effects .…”
Section: Prospects Of Tailored Colloidal Nanoparticles For Electrocat...mentioning
confidence: 99%
“…The selectivity towards CO formation was improved when the alloys were galvanically replaced with Ag. Yang et al 164 showed that bimetallic copper−lead (CuPb) electrocatalysts could be prepared from industrial metallurgical waste with the composition of Cu 9 Pb 1 , which exhibited a faradaic efficiency for CO formation that was four times higher than that of pure Cu. Indeed, using metal residues produced in the metallurgical industry to prepare electrocatalysts for CO 2 conversion is gaining more attention.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%